Antioxidant activity assay of stem and in vitro callusing of Tinospora cordifolia (Miers.) - A Bagga, M A Baigh, K C Verma, S Sapra, (Journal of Spices and Aromatic Crops, 2014)
The experiment was conducted to study the antioxidant potential among different hosts of Tinospora cordifolia. The results indicated that the among the different hosts of T. cordifolia, Ficus religiosa had highest phenol content (5.25 mg g-1), inhibition activity (52.05%) and reducing capability as compared to others. F. religiosa showed the highest antioxidant activity of 41.73 μM Fe (II) g-1. EC50 value for lipid peroxidation inhibitory activity was 0.1mg mL-1 for all the samples. EC50 value for DPPH radical scavenging activity was 0.6 mg mL-1 for F. religiosa. This results suggested that the active antioxidant compounds were higher in F. religiosa as compared to Roystonea regia. There was a direct correlation between the total polyphenols extracted and anti-oxidant activity. Among the various explants of F. religiosa, leaf explants were found to be superior for in vitro callus induction.